2021
DOI: 10.18553/jmcp.2021.27.10.1426
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing demographics, comorbidities, and costs of care among populations with Duchenne muscular dystrophy with Medicaid and commercial coverage

Abstract: BACKGROUND: Duchenne muscular dystrophy (DMD) is a severe X-linked progressive neurodegenerative disease characterized by loss of ambulation, cardiomyopathy, respiratory insufficiency, and early mortality. Few data are available that describe the direct medical costs among patients with DMD in the United States. OBJECTIVE: To characterize the demographics, comorbidity burden, and direct monthly costs of care among patients with DMD with Medicaid and with commercial insurance coverage. METHODS: IBM MarketScan C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This study was a US-based, real-world, retrospective cohort study to describe the clinical course of patients with DMD, treated under commercial health insurance plans. The study cohort and entry criteria were described previously in a study examining the characteristics of and economic burden among those with DMD in the US [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was a US-based, real-world, retrospective cohort study to describe the clinical course of patients with DMD, treated under commercial health insurance plans. The study cohort and entry criteria were described previously in a study examining the characteristics of and economic burden among those with DMD in the US [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…To describe the study sample, consistent with the previous analyses, [ 22 ] the demographic characteristics were summarized, and median duration of follow-up estimated. Health status over the follow-up period was summarized by the percentage observed with at least one prescription for corticosteroids; comorbidity burden (using the median with interquartile range [IQR] Elixhauser Index score, [ 33 ] and the frequency of individual Elixhauser comorbidities); and the prevalence of other key comorbidities of interest.…”
Section: Methodsmentioning
confidence: 99%
“…The MarketScan Research Databases have been effectively used in a variety of other studies to characterize patient populations with chronic disease, such as Fontan physiology, HIV, and cirrhosis, and to describe trends in resource use. 20 , 21 , 22 , 23…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we sought to evaluate the demographic and disease characteristics of patients who initiated novel DMD treatments in routine care in different insured populations and compare them with the patients enrolled in the drugs’ pivotal trials. Previous research has found similarities in demographic characteristics and medical costs between patients with DMD and commercial insurance and those with Medicaid coverage, but differences in relation to the costly new medications have not been studied …”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found similarities in demographic characteristics and medical costs between patients with DMD and commercial insurance and those with Medicaid coverage, but differences in relation to the costly new medications have not been studied. 13 …”
Section: Introductionmentioning
confidence: 99%